Control systems - Dukkipati, Rao V. (Alphascience International Ltd, 2005)
Control systems discusses in a concise but through manner fundamental statement of the theory, principles and methods for the analysis and design of control systems and their applications to real life practical control systems problems. Includes concepts and review of classical matrix analysis, Laplace transforms, modeling of mechanical, electrical, electromechanical, fluid and thermal systems, the process of converting a pictorial diagram to a block diagram, the time response of first and second order systems, stability, and frequency response approximation to the analysis and design of feedback control systems